Catalyzed carbon skeleton rearrangement of basic carbohydrates - Petruš, Ladislav; Hricovíniová, Zuzana; Petrušová, Mária; Matulová, Mária (Univerzita Pardubice, 2000)
The essentials of a remarkable carbon skeleton rearrangement of aldoses catalyzed with molybdic acid and known as the Bílik reaction are introduced. The extension of the reaction to a mutual interconversion of 2-ketoses and 2-C-(hydroxymethyl)-aldoses is also described. Finally, the molybdic acid catalysis is briefly compared with other known systems catalyzing similar transformations.
Keywords: organická chemie; organické reakce; Bílkova reakce; katalýza; přesmyky